Marginalizing Revolutionaries in Egypt's Civil State Debate. (2nd October 2018) - Magued, Shaimaa
Abstract : After President Hosni Mubarak was overthrown on February 11, 2011, competing narratives emerged about the Egyptian civil state during the formulation of the 2012 and 2014 constitutions. Arguably, the army's political domination and the Islamic–secular rivalry were behind the marginalization of young activists, militants in social movements, and many other civilians known as revolutionaries who took part in the January 25 Revolution, during the formulation of both constitutions. The following offers two new perspectives in the analysis of peaceful democratic transition in Egypt after the revolution. First, it relies on the analysis of the different actors' discourses about civil state in order to show how both constitutions overlooked the revolutionaries' vision and impeded peaceful democratic transition. Second, it addresses the civil state debate on which writings related to democratic transition in the Middle East remained silent and rather focusing on military–Islamist relations, the political economy of post-revolutionary regimes, and alliance shifts in foreign policy.